2016
DOI: 10.1038/srep19452
|View full text |Cite
|
Sign up to set email alerts
|

CRMAGE: CRISPR Optimized MAGE Recombineering

Abstract: A bottleneck in metabolic engineering and systems biology approaches is the lack of efficient genome engineering technologies. Here, we combine CRISPR/Cas9 and λ Red recombineering based MAGE technology (CRMAGE) to create a highly efficient and fast method for genome engineering of Escherichia coli. Using CRMAGE, the recombineering efficiency was between 96.5% and 99.7% for gene recoding of three genomic targets, compared to between 0.68% and 5.4% using traditional recombineering. For modulation of protein syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
171
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(176 citation statements)
references
References 58 publications
5
171
0
Order By: Relevance
“…This resulted in a labor-intensive and time-consuming procedure, especially for large-scale multiplex or iterative whole-genome engineering9 (Table 2). The use of short single-stranded DNA (ssDNA) as templates for recombineering that is independent of the selective marker greatly facilitated whole-genome engineering32, as exemplified by multiplex automated genome engineering (MAGE)3334. However, the genetic modification range of ssDNA recombineering is constrained by the length of the ssDNA, and large-scale chromosomal DNA fragment deletion is therefore not possible using that method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This resulted in a labor-intensive and time-consuming procedure, especially for large-scale multiplex or iterative whole-genome engineering9 (Table 2). The use of short single-stranded DNA (ssDNA) as templates for recombineering that is independent of the selective marker greatly facilitated whole-genome engineering32, as exemplified by multiplex automated genome engineering (MAGE)3334. However, the genetic modification range of ssDNA recombineering is constrained by the length of the ssDNA, and large-scale chromosomal DNA fragment deletion is therefore not possible using that method.…”
Section: Discussionmentioning
confidence: 99%
“…The CRISPR-Ca9 system has been broadly adopted in markerless genome engineering, and its utility and flexibility in genetic manipulation of the bacterial genome have improved dramatically34373839404142. Recently, Beier et al .…”
Section: Discussionmentioning
confidence: 99%
“…Two key mutations lrp D143G and rho R87L were introduced in Q1(DE3) thrA S357R strain separately using the CRMAGE system (Ronda et al, 2016). The pMAZSK plasmids containing gRNA targeting wild type lrp and rho was constructed using primers shown in Table S5.…”
Section: Reverse Engineering Of Key Mutations Found In Serine Toleranmentioning
confidence: 99%
“…The PCR product was subsequently phosphorylated with polynucleotide kinase, ligated with T4 DNA ligase and transformed. The isolated plasmids were used for the CRMAGE protocol (Ronda et al, 2016), and the resulting mutants were sequenced for targeted loci (by gF and gR primers listed in Table S5) and subjected for growth profiling studies.…”
Section: Reverse Engineering Of Key Mutations Found In Serine Toleranmentioning
confidence: 99%
“…Choi et al, T 2016;S. Choi et al, 2016;Park et al, 2011Park et al, , 2007Yim et al, 2011) owing to the rich toolset available for gene and expression modification (Datsenko and Wanner, 2000;Jiang et al, 2015;Ronda et al, 2016;Wang et al, 2009) as well as accumulated historical knowledge base of biochemical understanding (Guo et al, 2013;Kanehisa et al, 2017;Keseler et al, 2013;Monk et al, 2017). Seven commonly used strains in biotechnology applications include K-12 MG1655, K-12 W3110, K-12 DH5a, BL21, C, Crooks, and W. It has been shown that particular strains are better suited for different applications (Monk et al, 2016).…”
Section: Introductionmentioning
confidence: 99%